Virtual Job Fair Information System Design Based on Augmented Reality/Virtual Reality - Khairunisa, Yuyun; Nurhasanah , Yeni; Verlaili , Ratu (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Organizing a job fair is one of the steps to bridge the needs of companies in finding workers and the needs of job seekers to find work. Creative Media State Polytechnic (Polimedia) as a vocational college provides support to alumni to get decent jobs and according to their fields of expertise. In accordance with one of the Main Performance Indicators (KPI) of higher education, namely graduates get decent jobs [1]. However, currently Polimedia does not have a system that supports the implementation of the job fair or is still done manually. Research with the theme of developing virtual job fair information systems based on augmented reality and virtual reality has two objectives. The first objective is to develop an information system that assists the process of posting job vacancies and allows users to register for available vacancies. Then the second is to facilitate virtual job fairs. Because apart from the impact of the COVID-19 pandemic, holding a virtual job fair can be a distinct advantage for alumni who are looking for work because they can significantly save transportation and accommodation costs. The system development methodology used is the System Development Lyfe Cycle (SDLC) with the waterfall method. The waterfall method is divided into five stages, namely the analysis, design, implementation, testing and support stages. The design phase uses the Unified Modeling Language (UML), namely use case diagrams and entity relationship diagrams, while the implementation phase of augmented reality uses 3D modeling, markers and interface adjustments. In addition, the design of augmented reality and virtual reality applications uses the A-FRAME framework.